UJI EFEKTIVITAS EKSTRAK KULIT PISANG AMBON (Musaparadisiaca var. Sapientum L.) TERHADAP PERTUMBUHAN Trichophyton rubrum SECARA In Vitro - Rafliandi Nasruan Maulana (2020)
Dermatophytosis is a group of diseases caused by dermatophyte fungi, one of which is from the genus Trichophyton. Trichophyton rubrum is the most common cause of dermatophytosis worldwide, especially infecting humans. At this time many antifungal drugs are developed as an alternative therapy. This research was conducted to test the sensitivity of ambon banana peel extract (Musa paradisiaca var. Sapientum L.) on the growth of Trichophyton rubrum which was carried out using the method of wells using Sabouroud Dextrose Agar media with concentrations of 10%, 20%, 40% and 80% through four times treatment. The research took place at the Laboratory of Parasitology, Faculty of Medicine, UPN Veteran, Jakarta in November 2019. Based on the results of phytochemical tests, it was found that the compounds contained in the extract were tannin, phenolic, flavonoid, triterpenoid and glycoside. Each concentration showed a different average resistance response, where the highest concentration of 80% had an average inhibitory diameter of 4.52 mm. The inhibitory yield of 4.52 mm is included in the weak category because it is less than 5 mm. The Kruskal-Wallis test showed a value of 0.003 (<0.05) which meant that there were significant differences in results between treatment groups. The higher the concentration the stronger the inhibitory response. This research shows that the banana peel extract can inhibit the growth of the fungus T. rubrum.